Effects of Risk Management Practices on IT Project Success - Pimchangthong, Daranee; Boonjing, Veera (My University, 2017)
Successful management of an information technology (IT) project is the most desirable for all organisations and stakeholders. Many researchers elaborated that risk management is a key part of project management for any project size. Risk management is so critical because it provides project managers with a forward-looking view of both threats and opportunities to improve the project success. The objectives of this research are to explore organisational factors affecting IT project success and risk management practices influencing IT project success. Risk management practices include risk identification, risk analysis, risk response planning, and risk monitoring and control. The IT project success is measured by process performance and product performance. Data are collected from 200 project managers, IT managers, and IT analysts in IT firms through questionnaires and analysed using Independent Sample t-test, One-way ANOVA, and Multiple Linear Regression at the statistical significance level of 0.05. The results show that the differences in organisational types affect IT project success in all aspects, while the differences on organisational sizes affect IT project success in the aspect of product performance and total aspects. Risk identification and risk response planning influence the process performance and the total aspects of IT project success. Risk identification has the highest positive influence on product performance, followed closely by risk response, while risk analysis negatively influences product performance.
Keywords: information technology; project management; project success; risk management